2003
DOI: 10.1021/jm020582q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel, Selective GABAAα5 Receptor Inverse Agonist Which Enhances Cognition

Abstract: In pursuit of a GABA(A) alpha5-subtype-selective inverse agonist to enhance cognition, a series of 6,7-dihydro-2-benzothiophen-4(5H)-ones has been identified as a novel class of GABA(A) receptor ligands. These thiophenes have higher binding affinity for the GABA(A) alpha5 receptor subtype compared to the GABA(A) alpha1, alpha2, and alpha3 subtypes, and several analogues exhibit high GABA(A) alpha5 receptor inverse agonism. 6,6-Dimethyl-3-(2-hydroxyethyl)thio-1-(thiazol-2-yl)-6,7-dihydro-2-benzothiophen-4(5H)-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 23 publications
4
130
0
Order By: Relevance
“…Standard tests of locomotor activity were not usually employed in reported studies with α5 subunit-selective ligands (Atack et al, 2006a;Chambers et al, 2003;Collinson et al, 2006;Dawson et al, 2006). Based on the results with three novel BZ site agonists functionally silent at the α1 subunit, we recently set out the hypothesis that positive modulation at the GABA A receptors containing α5 subunits may contribute to sedative properties of BZ site agonists (Savić et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard tests of locomotor activity were not usually employed in reported studies with α5 subunit-selective ligands (Atack et al, 2006a;Chambers et al, 2003;Collinson et al, 2006;Dawson et al, 2006). Based on the results with three novel BZ site agonists functionally silent at the α1 subunit, we recently set out the hypothesis that positive modulation at the GABA A receptors containing α5 subunits may contribute to sedative properties of BZ site agonists (Savić et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that GABA A receptors containing the α5 subunit are abundantly expressed in the hippocampus (Pirker et al, 2000;Sieghart and Sperk, 2002), the structure substantially involved in memory formation (Izquierdo and Medina, 1997). Recent evidence from animal studies with affinity-selective (Atack et al, 2006a) or efficacy-selective ligands (Chambers et al, 2003;Dawson et al, 2006 has confirmed that the α 5 subunit was significantly involved in cognition enhancement mediated by the negative modulation of GABA A receptor functions. Moreover, it was shown in humans that pre-treatment with an α 5 efficacy-selective inverse agonist significantly reduces the amnesic effect of alcohol on learning a word list (Nutt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using point mutation knock-in mice, it has been reported that GABA A receptors including the α1 subunit mediate the acute sedative (Rudolph et al, 1999;Mckernan et al, 2000) and in part the anticonvulsant (Rudolph et al, 1999) action of diazepam, while the anxiolytic effect is mediated by α2-containing GABA A receptors (Low et al, 2000). The α5 GABA A receptor subunit which is highly expressed in hippocampus, including the CA1 and CA3 regions, plays a significant role in spatial memory performance (Chambers et al, 2003;Rudolph and Mohler, 2004), freezing response in trace but not delay fear conditioning (Crestani et al, 2002b), and in fear conditioning extinction (Yee et al, 2004;Crestani et al, 2002b). In contrast, GABA A receptors including the α2, α3 or α5 subunits that are located on motor neurons and in the dorsal horn of the spinal cord are believed to mediate the muscle relaxant and anti-hyperalgesic actions of diazepam (Bohlhalter et al, 1996;Crestani et al, 2001;Knabl et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we focus on α5-containing GABA-A receptors, as these receptors are highly expressed in brain regions substantially involved in memory formation and emotion [8][9][10]. Previous evidence from animal studies has shown that the α5-containing GABA-A receptors were signifi cantly involved in cognition [11][12][13][14]. Moreover, it has been shown that a negative modulation of α5 GABA-A receptors may represent an attractive treatment option for cognitive impairments, and potentially positive symptoms, associated with schizophrenia [15].…”
Section: Research Articlementioning
confidence: 99%